A summary of modeling studies of the Nesjavellir geothermal field, Iceland - Bodvarsson, G.S.; Bjornsson, S.; Gunnarsson, A.; Gunnlaugsson, E.; Sigurdsson,, O. Stefansson, V.; Steingrimsson, B. (Lawrence Berkeley Laboratory, 1988)
The Nesjavellir geothermal field in Iceland is being developed to provide the capital city of Reykjavik and surrounding areas with hot water for space heating. In the last few years, many wells have been drilled at the site and various geothermal studies have been conducted. The main upflow to the system is underneath the nearby Hengill volcano, and the natural recharge rate and enthalpy are estimated to be 65 kg/s and 1850 kJ/kg, respectively. An extensive vapor zone is believed to be present in the upflow region. Permeabilities and porosities of the system range between 1 and 50 md and 1 and 10 percent, respectively. In this paper, the characteristics of the Nesjavellir field are described and a three-dimensional numerical model of the resource in discussed. 15 refs., 11 figs., 1 tab.